Dari Pengawasan Ke Pemuridan: Menggali Fungsi Teologis Supervisi Pelayanan Dalam Pertumbuhan Pelayan Gereja - Gulo, Wa'azaro (Vieka Wahana Semesta, 2025)
Supervision in ministry is an essential aspect of developing and improving the performance quality of church ministers such as Elders, Pastors, Deacons, and Sunday School teachers. This article examines the concepts, purposes, strategies, and challenges of ministry supervision within the Indonesian church context, with a particular focus on the ONKP Church (Orahua Niha Keriso Protestan) as the primary object of study. Within the ONKP Church, supervision is understood as a pastoral process that not only guides the spiritual growth of church workers but also supports their professional development in accordance with ONKP’s organizational structure and ministerial traditions. Through planned, contextual, and continuous supervision, the quality of teaching and ministry can be significantly enhanced amid the dynamics of ONKP congregations spread across various regions. This study employs a descriptive qualitative approach to evaluate the effectiveness of supervision in developing ministry workers within the ONKP Church. The findings indicate that supervision contributes substantially to improving both the spiritual and professional competence of ONKP ministers, particularly when implemented through reflective guidance, ongoing evaluation, and strong community support. However, challenges such as limited human resources, the diverse contexts of ONKP congregations, and insufficient understanding of supervision as an integral component of ministerial formation remain significant obstacles. These findings highlight the need for a more systematic and adaptive supervisory model to strengthen ministry quality within the ONKP Church.